Varying strategies to maximize the effectiveness of ELT: Lessons from training sessions - A. Dzo'ul Milal; Zuliati Rohmah; Wahju Kusumajanti (Universitas Ahmad Dahlan, 2020)
Several factors determine the effectiveness of language learning, one of which is the variety of strategies carried out by the teacher in the teaching and learning process. Defined as any efforts made to maximize the learning achievements, strategy encompasses material development, classroom management, and teaching techniques. The question is in what ways the teacher implements such a variety, and what the effect is.This descriptive study was conducted in an in-service teacher training which aimed to improve the trainees’ mastery of ELT strategies and the teaching language. The data were collected using questionnaires, observation, documentation, interviews, and reflection. The subjects were the trainers and the teacher trainees who have mixed language abilities and teaching experiences.The findings show a range of varieties was employed during the training process, covering the use of diverse materials, fun classroom activities, learner-centered approach, affect-lowering classroom management, and varied interaction patterns. As effective learning is dependent on the fresh minds, teachers should always strive to prevent their students from exhausting monotony.